HARVEST AND POST-HARVEST HANDLING TECHNIQUES OF SWEET PLANT (Brassicia juncea L.) BY HYDROPONIC FLOWERS - Harahap, Evi Julianita; Tumanggor, Amitalia; Siregar, Mawaddah Putri Arisma; Afrillah, Muhammad; Saputra, Juldi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Proper harvest and post-harvest handling techniques can influence the quality of the harvest, such as cleanliness, freshness and visual quality. In hydroponic mustard cultivation, harvest and post-harvest handling is very important because hydroponic mustard plants require special treatment to ensure the quality of the harvest. The research was carried out at the UF (University Farm) Land of Teuku Umar University, West Aceh Regency in October 2023. Procedures for carrying out the research included harvesting, washing and removing manure, sorting, packaging, cooling and storage, transportation, marketing. The conclusions are (1) good harvesting is done in the morning and evening to avoid sunlight which can trigger wilting of mustard plants and (2) good packaging can increase the safety of products that will be marketed to consumers.